Pengaruh Green Marketing, Store Atmosphere Dan Quality Product Terhadap Purchase Decision Pada Produk Eiger (Studi pada mahasiswa FEB Universitas Islam Malang) - Krisnawardani, Cynthia; Susyanti, Jeni; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study is to analyze the impact of Green Marketing, Store Atmosphere, and Quality Product on Purchase Decision of Eiger products among students of the Faculty of Economics and Business at the Islamic University of Malang who have visited and purchased Eiger products. The sample consists of 87 respondents, selected using purposive sampling, and researched using multiple linear regression. Findings of this research partially indicate that Green Marketing, Store Atmosphere, and Quality Product have a significant positive effect on the Purchase Decision of Eiger products. Keywords: Green Marketing, Store Atmosphere, Quality Product, Purchase Decision, Eiger.